Case report: Neoplasma kista ovarium - Fernando, Ego; Triansa , Nabila Farah; Purwiandari, Hervyasti (Institute of Computer Science (IOCS), 2024)
Ovarian cysts are fluid-filled sacs that can develop in various body regions, with unknown prevalence due to many cases being asymptomatic. Approximately 4% of women may be hospitalized for an ovarian cyst by age 65. This case report details a 45-year-old woman presenting with abdominal pain during menstruation, an enlarged and hard stomach, a painful breast lump, back pain, defecation difficulties, and discomfort during intercourse. Diagnostic examinations revealed a large ovarian cyst with associated symptoms. Cysts on the ovaries are generally discovered accidentally when the patient is having a routine check-up or other gynecological examination. This is caused by ovarian cysts which can be asymptomatic, especially when they are small. If there is suspicion of an ovarian cyst or a mass is found, it is necessary to continue with a physical examination in the form of TTV, abdominal examination and internal examination. Further research is needed to determine the etiology of ovarian cysts and their treatment.